Mismatching among guidelines, providers, and parents on controller medication use in children with asthma - Wu, Ann Chen (J Allergy Clin Immunol Pract, 2016)
BACKGROUND: Underuse of controller medicines among children with asthma remains widespread despite national guidelines. OBJECTIVES: To: (1) assess provider prescribing patterns for asthma controller medications; (2) assess how frequently parents’ reports of their child’s asthma controller medicine use were mismatched with their provider’s recommendations; and (3) evaluate parent attitudes and demographic characteristics associated with these mismatches. METHODS: In this cross-sectional study, we conducted linked surveys of parents and providers of children with probable persistent asthma in a Medicaid program and four commercial health plans in 2011. Probable persistent asthma was defined as a diagnosis of asthma and ≥1 controller medication dispensing. RESULTS: This study included 740 children (mean age 8.6 years). Providers for 50% of the children reported prescribing controller medications for daily year-round use, 41% for daily use during active asthma months, and 9% for intermittent use for relief. Among parents, 72% knew which class of controller medication the provider prescribed and 49% knew the administration frequency and the medication class. Parents were less likely to report the same controller medication type as the provider, irrespective of dose and frequency, if they were Latino [OR 0.23; CI 0.057–0.90], had a household smoker [OR 2.87; CI 0.42–19.6], or believed the controller medicine was not helping [OR 0.15; CI 0.048–0.45]. CONCLUSIONS: Mismatches between parent reports and providers’ intentions regarding how the child was supposed to use inhaled steroids occurred for half of children. Efforts should focus on ways to reduce mismatches between parent and provider intentions regarding controller medication use.